City and Energy Infrastructures between Economic Processes and Urban Planning - Giuseppe Mazzeo (TeMA: Journal of Land Use, Mobility and Environment, 2013)
The paper deals with the issues related to the relationship between city, energy, economic factors and city planning. These issues are analyzed from a theoretical point of view and are placed in a logical path based on three assumptions. The first considers the city as an intelligent system constantly evolving. The second considers the city as a system where economic processes come out at their highest level affecting other aspects of social and urban structure. The third considers the planning as the weak link in the process of urban development, one of the most exposed to economic and social pressures. Energy production has experienced a great progress since steam and electricity were discovered. Each stage of this evolution has affected city and territory introducing significant physical signs, changing the ways of carrying out functions and creating new needs and new activities. The energy revolution, based on sustainable sources and on skillful management of the networks, will strongly affect the city and the way of organizing the activities, their location, dimension, and the shape of the spaces. The paper explores some of the issues related to the relationship between urban system and energy. The first section analyzes the meaning of the intelligent city as an entity that is constantly changing and constantly adapting. The second section analyzes the role of the energy systems in the evolution of the activities and of the city’s image. The last section investigates the role of the economic factors in the evolution of the shape and meaning of city, pointing out that the way towards smart and green urban systems will largely depend on their economic advantage.